Snowball‐like appearance on radial endobronchial ultrasonography in a patient with invasive mucinous adenocarcinoma. Issue 4 (8th March 2021) - Kawaguchi, Takeshi; Himeji, Daisuke; Beppu, Kiichio; Marutsuka, Kousuke
Abstract: Invasive mucinous adenocarcinoma (IMA), which is a relatively rare lung adenocarcinoma, is considered a high‐grade subtype and is associated with a poor prognosis. IMA is difficult to diagnose by computed tomography because it requires differentiation from inflammatory diseases, such as atelectasis, infectious pneumonia, and organizing pneumonia. Thus far, no reports of radial endobronchial ultrasonography (EBUS) findings in IMA have been published. This article presents a case of IMA with a characteristic shadow, snowball‐like appearance on radial EBUS in a 67‐year‐old Japanese man. Abstract : Invasive mucinous adenocarcinoma (IMA), which is a relatively rare lung adenocarcinoma, is difficult to diagnose by computed tomography. No reports of radial endobronchial ultrasonography (EBUS) findings in IMA have been published. This article presents a case of IMA with a characteristic shadow, snowball‐like appearance on radial EBUS in a 67‐year‐old Japanese man.